Inovasi Permainan Digital dalam Meningkatkan Kepekaan Remaja terhadap Isu Lingkungan - Pramesthi, Jasmine Btari; Susanti, Elizabeth (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
With the development and ease of people accessing technology, digital games are a means of entertainment that is easy for teenagers to access and have many positive impacts, one of which is being a means of education about environmental issues such as global warming. Educational facilities using digital games are often called Digital Game-Based Learning (DGBL). This research aims to realize the potential of digital games as an educational medium to increase teenager's sensitivity to environmental issues. The method used is the literature study method. The novelty offered by this writing is to find out how to utilize the potential of digital games to be applied to environmental issues that are currently developing in Indonesia to increase adolescent knowledge.